The Effectiveness of Podcast Application in the Teaching of Listening. - Ayu Atikah Sari (Language-Edu, 2021)
A Podcast application is software that can be downloaded from play store or app store. A podcast allow students to practice English more comfortably. By using podcast applications as an effective media to develop the students’ listening skills. The objective of this research is to find out the effectiveness of podcast application to developing students’ listening skills. The sample of this research consisted of 25 students at IX grade of MTS SalafiyahSiman. The instrument of this research is a test. The quantitative data were in the form of students’ listening scores. The scores are comparing from pre-test and post-test. To achieve the purpose of this study, the data were analyzed by using paired sample t-test in the SPSS program. After analyzing the test, the researcher found that the mean score of the post-test is greater than the pre-test (77.88 for the post-test and 57.64 for the pre-test). And the results of calculating using paired t-test, the results obtained are sig.2 tailed of .000 < .05 with t-count of -9.276 which means that the average before using podcast application is lower than the average after using podcast. Thus, podcast application gives effective learning in the students’ listening skill.